Designing Probiotic Therapies With Broad-Spectrum Activity Against a Wildlife Pathogen - Harrison, Xavier A.; Sewell, Thomas; Fisher, Matthew; Antwis, Rachael E. (Frontiers in Microbiology, 2020)
Host-associated microbes form an important component of immunity that protect against infection by pathogens. Treating wild individuals with these protective microbes, known as probiotics, can reduce rates of infection and disease in both wild and captive settings. However, the utility of probiotics for tackling wildlife disease requires that they offer consistent protection across the broad genomic variation of the pathogen that hosts can encounter in natural settings. Here we develop multi-isolate probiotic consortia with the aim of effecting broad-spectrum inhibition of growth of the lethal amphibian pathogen Batrachochytrium dendrobatidis (Bd) when tested against nine Bd isolates from two distinct lineages. Though we achieved strong growth inhibition between 70-100% for seven Bd isolates, two isolates appeared consistently resistant to inhibition, irrespective of probiotic strategy employed. We found no evidence that genomic relatedness of the chytrid predicted similarity of inhibition scores, nor that increasing the genetic diversity of the bacterial consortia could offer stronger inhibition of pathogen growth, even for the two resistant isolates. Our findings have important consequences for the application of probiotics to mitigate wildlife diseases in the face of extensive pathogen genomic variation.